Comparative Analysis of User Satisfaction Levels on Livin By Mandiri and BSI Mobile Applications Using the PIECES Method - Ayu, Sahira Putri (Jurnal Pamator : Jurnal Ilmiah Universitas Trunojoyo, 2023)
In social life, transactions are inseparable from humans. In general, exchange activities, means of payment for goods, are gradually being replaced in the modern world with the presence of banks to facilitate all human transactions. The facilities provided by banks centrally are Mobile Banking (M-Banking) or banking services through digital or mobile phones that function almost like ATMs. Livin By Mandiri and BSI Mobile are among the mobile banking providers with around 62 million users. As a new thing that has just entered the country, mobile banking, especially applications launched for the needs of the community, requires satisfaction analysis. Aiming at these issues, this study examines the effectiveness and efficiency of the system from the following aspects: User interface convenience. The following research aims to analyze user satisfaction of Livin By Mandiri and BSI Mobile mobile banking applications. User satisfaction analysis is determined using qualitative research methods and PIECES or performance, information and data, economy, control and safety, efficiency, service methods. The results showed that both applications had good performance according to PIECES indicators, but in terms of information, BSI Mobile outperformed Livin By Mandiri in the category and the Livin By Mandiri application outperformed BSI Mobile in terms of efficiency. With these satisfactory results, Livin By Mandiri and BSI Mobile can be said to be very good and this value must be maintained.